A Guide to Greater Cleveland's Sacred Landmarks - Ellis, Lloyd H., Jr., 1936- (Book collections on Project MUSE., 2012)
An informative guide to the Cleveland area?s houses of worship The sacred landmarks of Cleveland and the surrounding area provide a fascinating array of architectural styles and often serve as visual focal points and social centers in the area?s many ethnic communities. In A Guide to Greater Cleveland?s Sacred Landmarks, author Lloyd Ellis describes the origins of the area?s religious communities, outlines the history of their buildings, interprets their architectural styles, and provides details on significant interior features. Ellis profiles seventy-five Protestant churches, fifty-seven Catholic churches, eight Jewish institutions, eight Orthodox churches, three Mosques, two Unitarian churches, and a Hindu temple, and provides readers with fifteen recommended tours around Cuyahoga County. He describes each structure by explaining its importance as a religious, cultural, or architectural landmark, and accompanies each entry with an exterior photograph. In addition to serving as a reference to thriving religious institutions, A Guide to Greater Cleveland?s Sacred Landmarks preserves the memory of the area?s extinct or endangered religious communities, passing the stories of past generations to generations in the future. Anyone interested in greater Cleveland?s architectural, religious, and ethnic history will welcome this well-researched and richly illustrated guide.